2014
DOI: 10.1002/anie.201408852
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐Pyridyl‐5,15‐Diazaporphyrin Nickel(II) Complex as a Bidentate Metalloligand for Transition Metals

Abstract: 3-Pyridyl-5,15-diazaporphyrin nickel(II) serves as a bidentate metalloligand for platinum(II), ruthenium(II), and rhenium(I) metal centers. Single-crystal X-ray diffraction analysis of these metal complexes unambiguously reveals the presence of a dative bond between the outer metal center and the meso-nitrogen atom. The UV/Vis absorption spectra of the complexes show substantially red-shifted bands which are perturbed by outer-metal coordination. This is due to the contribution of metal-to-ligand charge transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…This result supported the idea that both moieties are behaving independently upon light interaction, expressed through their steady state photophysical properties. Differently, from other metal macroring complexes [49], the herein investigated system showed that although porphyrin and ruthenium moieties are physically attached, the weak coupling through the pyridine bridges hinders intramolecular interactions such as electron and energy transfer.…”
Section: Steady State Spectroscopymentioning
confidence: 59%
“…This result supported the idea that both moieties are behaving independently upon light interaction, expressed through their steady state photophysical properties. Differently, from other metal macroring complexes [49], the herein investigated system showed that although porphyrin and ruthenium moieties are physically attached, the weak coupling through the pyridine bridges hinders intramolecular interactions such as electron and energy transfer.…”
Section: Steady State Spectroscopymentioning
confidence: 59%
“…[7] 5,15-Diazaporphyrins (1M,S cheme1;M= Ni or 2H)a re 18 p porphyrinoidsw ith imine-type sp 2 -hybridizedn itrogen atoms at the meso positions. [8,9] Because of its relatively low-lying LUMO, 1M is pronet ou ndergo nucleophilica dditiono fa lkyllithiumr eagents. [8b] This characteristicf eature of 1M prompted us to explore the reaction of 1M with variousr eductants.…”
mentioning
confidence: 99%
“…The absorption spectra of 3Ni and 3H 2 exhibit as ubstantially different shapef rom those of 1Ni and 1H 2 . [8] In particular,w eak absorption bands were detected at l = 700-1200 nm (dashed lines) and are assigned to the characteristic forbidden bands that are typical for antiaromaticp orphyrinoids. [19] The electrochemical properties of 3Ni and 3H 2 were examined by using cyclic voltammetry (see the Supporting Information,F igure S13).…”
mentioning
confidence: 99%
“…TD-DFT calculations showed that the lowest-energy absorption bands mainly derive from the HOMO to LUMO transition and the transition involves acertain charge transfer character from porphyrin (face) to the Pd II -triphyrin site (ear), suggesting some contribution of d-p conjugation (see the Supporting Information). [13] Cyclic voltammetry and differential-pulse voltammetry experiments have been conducted in CH 2 Cl 2 against af errocene/ferrocenium ion couple.All the new earring porphyrins displayed more than four peaks as listed in Table 1a nd the Supporting Information, Figures S20-S22. Thef used earring porphyrins 4Pd and 8Pd showed negatively shifted first oxidation potentials and positively shifted first reduction potentials as compared with their non-fused earring porphyrins 3Pd and 7Pd.Asar esult, 4Pd and 8Pd exhibited smaller electrochemical HOMO-LUMO gaps of 0.80 eV for 4Pd,and In summary,t he designed fabrications allowed for the construction of doubly 2,3-thiophene-fused and 2,3-pyrrolefused earring porphyrins 4Pd and 9Pd.D oubly 1,2-pyrrolefused earring porphyrins 5H and 5Pd were also synthesized.…”
Section: Methodsmentioning
confidence: 99%
“…[13] Cyclic voltammetry and differential-pulse voltammetry experiments have been conducted in CH 2 Cl 2 against af errocene/ferrocenium ion couple.All the new earring porphyrins displayed more than four peaks as listed in Table 1a nd the Supporting Information, Figures S20-S22. [13] Cyclic voltammetry and differential-pulse voltammetry experiments have been conducted in CH 2 Cl 2 against af errocene/ferrocenium ion couple.All the new earring porphyrins displayed more than four peaks as listed in Table 1a nd the Supporting Information, Figures S20-S22.…”
Section: Porphyrins Fused With Aromatic Units Have Attracted Increas-mentioning
confidence: 99%